2018
DOI: 10.3184/175815618x15180876264262
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprotective Effect of Glycerol Concentrations on Indian Red Jungle Fowl (Gallus Gallus Murghi) Spermatozoa

Abstract: Semen cryopreservation protocols for wild avian species need to be optimised in order to achieve optimum post-thaw sperm quality and fertility. The present study was designed to evaluate the cryoprotective effect of different glycerol concentrations (11%, 15% and 20%) on post-thaw quality, recovery rates, absolute livability index and fertility of Indian Red Jungle Fowl (Gallus gallus murghi) semen. Semen was collected from eight mature cocks and cryopreserved for storage at −196 °C. Frozen semen was thawed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…On the one hand, condensed chromatin structure therefore gradually decondenses in DMSO-treated cells, giving rise to cells with normal (physiological) chromatin. In samples cryoprotected with glycerol, 43 on the other hand, both proportions of cells with condensed chromatin and cells with viable chromatin have fallen dramatically at 2.5 h after thawing, suggesting death of most cells. This proportion of cells that persisted with condensed chromatin at 2.5 h post-thawing wellcorrelated with the percentage of viable cells as measured by flow-cytometry (Annexin V/PI positivity at 0.5 h postthawing).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the one hand, condensed chromatin structure therefore gradually decondenses in DMSO-treated cells, giving rise to cells with normal (physiological) chromatin. In samples cryoprotected with glycerol, 43 on the other hand, both proportions of cells with condensed chromatin and cells with viable chromatin have fallen dramatically at 2.5 h after thawing, suggesting death of most cells. This proportion of cells that persisted with condensed chromatin at 2.5 h post-thawing wellcorrelated with the percentage of viable cells as measured by flow-cytometry (Annexin V/PI positivity at 0.5 h postthawing).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results of the study suggest that the semen cryopreservation method for IP-Khaki semen needs further optimization. The type of diluent, as well as the type and inclusion level of cryoprotectant, may be modified again to obtain better results (Gerzilov, 2010;Rakha et al, 2018;Di Iorio et al, 2020). Previously reported studies on rooster semen cryopreservation showed that the inclusion levels of DMSO or glycerol can vary depending on the cryopreservation procedure and the animal breed used, suggesting that a single protocol will not always work for all breeds (Blanch et al, 2014;Khaeruddin et al, 2019;Long et al, 2010;Pelaez et al, 2011;Svoradová et al, 2018;Telnoni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After being held at 5°C for 2 h, the extended semen samples were divided into two equal volumes and assigned to two types of cryoprotectant (i.e., DMSO or glycerol). Each cryoprotectant was mixed with LFSE and added to the extended cooled semen to a final inclusion rate of 4.5% for DMSO (Vivantis Inc., USA) as adopted from Van Voorst et al (1995) and 7.0% for glycerol (Life Technologies Corp., USA) as adopted from Rakha et al (2018). The ejaculates were diluted to a final concentration of 2.00 × 10 8 sperm/mL and held again at 5 °C for another hour, instead of two hours.…”
Section: Semen Cryopreservationmentioning
confidence: 99%
“…Hence, the obtainment of an effective semen cryopreservation protocol in avian species represents a key point for ensuring the long-term conservation of genetic diversity through the creation of a semen cryobank. Different freezing procedures have been developed to cryopreserve avian semen [4,8,[15][16][17][18][19]. Effective semen cryopreservation protocols have allowed the creation of semen cryobanks for various wild and some domestic chicken species [3,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%